Analysis of a Solar Cookers Box-Type with inner reflectors by using CFD. Issue 1 (1st September 2022) - Terres, H; Chávez, S; Lizardi, A; Lara, A; Morales, J; Rodríguez, R; Ruiz, C; Reyes, M; Andrade, E
Abstract: This work shows the results and evaluation of a solar cooker box-type by using CFD. The values indicate where the highest temperature values happen inside the solar cooker. Also, values for density and airspeed were obtained. These results show where and how density and airspeed have the most important values during the water heating process. The effects of convection as a consequence of the temperature difference can guide possible improvements in future designs of solar cookers since if geometric shapes are used that take advantage of this heat transfer mechanism, the solar heating process can be better.